District based flood risk assessment in Istanbul using fuzzy analytical hierarchy process - Ekmekcioglu, Omer; Koc, Kerim; Ozger, Mehmet (SPRINGER, 2021)
Floods, among the most frequent and severe hazards in the world, threaten the sustainability of the built environment by causing immense damage to infrastructures, buildings, economies, social activities and beyond all, cause loss of lives. Istanbul is the most densely populated industrial, commercial and cultural center of Turkey. Besides, the population of Istanbul has increased over the last decade since the city attracts immigrants from all over Turkey, along with other countries. Therefore, it is vital to prioritize the districts of Istanbul by determining flood risk mitigation strategies since flood risk management is carried out at district level units in local municipalities in Istanbul. In this study, a new hierarchical procedure that consists of thirteen flood vulnerability and hazard criteria is proposed for the generation of Istanbul's district-based flood risk map. To obtain the criteria weights the fuzzy analytical hierarchy process (AHP) was adopted. The sensitivity analysis conducted in this study reveals the stability and robustness of the proposed fuzzy AHP model. Among all the criteria, land use and the return period of a storm event were found as the most significant criteria for vulnerability and hazard clusters, respectively. Criteria weights calculated through the fuzzy AHP method were integrated with the data taken from various institutions with respect to each district to calculate risk scores of the districts. Consequently, district risk scores were used to generate a flood risk map of Istanbul. The findings show that high-risk districts are mainly at the center and highly populated areas of the city. Moreover, the accuracy of the proposed approach was validated through observations of the significant flood events experienced in the last two decades. Thus, the fuzzy AHP method can be considered as advantageous to make a quick and regional flood risk assessment. In addition, the proposed approach is useful to mitigate flood risk along with allocating a fair budget to the local municipalities for flood risk mitigation measures. The findings of this research could also provide useful procedures for professionals of the water resources and local authorities.
Keywords: Flood risk mapping; Fuzzy analytical hierarchy process; Istanbul; District prioritization; Vulnerability and hazard; Sensitivity analysis; IMPACT ASSESSMENT; DECISION; AHP; VULNERABILITY; URBANIZATION; EXPERT; Engineering; Environmental Sciences & Ecology; Mathematics; Water Resources